Secondary Vitrectomy with Internal Limiting Membrane Plug due to Persistent Full-Thickness Macular Hole OCT-Angiography and Microperimetry Features: Case Series - Dominika Wrzesińska; Katarzyna Nowomiejska; Dominika Nowakowska; Mario Damiano Toro; Vincenza Bonfiglio; Michele Reibaldi; Teresio Avitabile; Robert Rejdak (Journal of Ophthalmology)
Purpose. To study the features in OCT-angiography and microperimetry in eyes with persistent full-thickness macular hole (FTMH) closed with the secondary plana vitrectomy (PPV) with autologous internal limiting membrane (ILM) plug. Methods. Secondary PPV was performed with closing the persistent FTMH with ILM plug, C3F8 tamponade, and face-down positioning. Four patients were followed for 6 months with best corrected visual acuity (BCVA) measurement, SD-OCT and OCT-A, and microperimetry. The results were compared with the fellow eye; in two patients, it was the healthy eye, and in two remaining eyes, successfully closed FTMH after primary PPV. Results. ILM flap was integrated in all cases with V-shape of closure, and atrophy was found in one case, with the largest diameter of FTMH. BCVA improved in two cases and remained the same in two cases. In OCT-A, the area of foveal avascular zone (FAZ) was larger, and foveal vessel density (FVDS) was smaller in eyes after secondary PPV in comparison to fellow eyes. In microperimetry, retinal sensitivity was lower in eyes after secondary PPV, and eccentric fixation was found in 2 of 4 patients. Conclusion. Although the anatomical results of repeated surgeries of FTMH with ILM plug are favorable, visual function results may be limited. Secondary closure of FTMH with ILM plug may lead to atrophy, changes in the macular vasculature, and eccentric fixation. The trial is registered with NCT03701542.